Primary education teachers’ perceptions about parental involvement in border schools» - Πορταΐτισσα Πετρίδενα Αγγελίνα; Γερακοπούλου Πατρίτσια (Education Sciences, 2024)
The aim of the research is to study the experiences of teachers serving in Primary schools in the border on issues related to parental involvement in the educational process. Semi- structured interviews were conducted with ten female teachers serving in two border areas, in order to highlight experiences and meanings regarding the participation of parents in school life. The interview material was transcribed and subjected to thematic analysis. Research showed that the participants perceive parental involvement as a continuous, two-way communication between parents and teachers, with the basic forms of parents' participation in the children's homework, and their active involvement in school life. The perceptions, attitudes and beliefs of the parties involved as they develop in the context of the special culture of these two regions emerged as factors in this formation.